Analysis of Coordination Mode of Dual-channel Experience Service Based on Product Experience - Luo, Siqin; Liu, Beibei (International Journal of Accounting and Financial Reporting, 2023)
From the perspective of product experience, product pricing and service strategy models of online sales channels and offline sales channels are established to analyze the influence of product experience and consumer free-riding behavior on the product experience and service level of online sales channels and offline sales channels. Then it analyzes the decision-making of centralized decision-making mode and decentralized decision-making mode of offline and offline dual-channel experience service. The results show that when the product experience coefficient is low, that is, the more consumers need to experience to determine the value of the product, the manufacturer should promote the service cooperation of product experience through both online and offline channels, and adopt a centralized decision-making mode. On the contrary, the decentralized decision-making mode should be adopted. In the centralized decision-making mode, the offline sales channel product experience service level is higher than its online product experience service level; When consumers have a lot of free-riding behavior, the level of dual-channel product experience service should be improved, and vice versa.